26. A public park is in the shape of a triangle. The side of the park that forms the base of the triangle is 2000 yards long, and the area of the park is 7500 yards2 . What is the length of the side of the park that forms the height of the triangle?

Answers

Answer 1
Answer:

Answer:

7.5 yards

Step-by-step explanation:

Since the area of a triangle is found by the equation: (bh )/(2), in which b=base h=height, and bh is base times height, we can work backward from the value of the area to find the height of the park

Start by multiplying 7500 by 2. From this, you get 15000.

Now for the second step, you have to divide 15000 by 2000 in order to determine the height of the triangle. this value comes out to 7.5.

This means that the values of the equation are b=2000 and h=7.5  (2000(7.5))/(2)

To double-check, we multiply 2000 by 7.5. and divide that value by 2. This gives us the original area of 7500

This means that the height of the park is 7.5 yards


Related Questions

How are fractions and decimals related
What is the least common denominator (LCD) of 9/10 and 5/8?
A local discount store is famous for their motto, "Shop with us and you'll pay 20% less". Their claim is that every item in the store is already marked down 20% off of retail prices. In this Sunday's ad, they are advertising a scuba mask and snorkel set at their discount price of $28. Use a percent model to determine the original retail price of the scuba mask and snorkel set.
How could you estimate the number of M&M's in a jar? (check all that apply)acount thembcount a sample and estimate the number of times it would take to fill using the samplecthe area of the jar divided by the area of an M&Mdmeasure the height of the jarethe volume of the jar divided by the volume an M&M
a jar containing only nickels an dimes contains a total of 60 coins. The value of all the coins in the jar is $4.45. What is the number of nickels and dimes in the jar?

Given the function f(x) = 4 - 2x: If the domain is {-4, 0, 5}, find the range. A) {-4, 4, -6} B) {-4, 4, 14} C) {12, 4, -6} D) {12, 4, 14)

Answers

f(x) = 4 - 2x                   Domain = x = -4, 0, 5

f(x) = 4 - 2(-4) = 4 - (-8) = 12  

f(x) = 4 - 2(0) = 4 - 0 = 4

f(x) = 4 - 2(5) = 4 - 10 = -6

f(x) = 12, 4, -6

The range is C. 
It's C. Good luck on your finals!

Please solve this -2x + 12y - 4

Answers

2 (2x - (2 - 2y + 3x) + 4y) =
2 (2x - 2 - 2y + 3x + 4y) =
2 (5x + 2y - 2) =
10x + 4y - 4
This was my solution.

The products of 0.42 with 0.2 can be written in fraction?Yes or no and whats the right fraction i keep get it wrong​

Answers

I believe it is yes. I think the right fraction is 84/1000. Let me know if this works and if not tell me

Answer:

yes ... 42/100 × 2/10= 21/250

The cubic parent function y=x^3 contains the point (2,8). If the function reflected over the x-axis and shifted right 6 units, what are the coordinates of the new point

Answers

Answer:

The new coordinate are (8,-8)

Step-by-step explanation:

Whenever a graph is reflected about the x-axis, positive y values become negative and vice versa. In this case positive y(8) becomes negative (-8). While the x values remain unchanged.

So the coordinates when moving by one unit will be (2,-8)

Shifting it 6units to the right increases the x values by six to give the new coordinates which is (8,-8)

Review the incomplete derivation of the cosine sum identity.A 2-column table with 5 rows. Column 1 has entries step 1, step 2, step 3, step 4, step 5. Column 2 has entries cosine (x + y), sine (StartFraction pi Over 2 EndFraction minus (x + y) ), blank, sine (StartFraction pi Over 2 EndFraction minus x) cosine (negative y) + cosine (StartFraction pi Over 2 EndFraction minus x) sine (negative y), blank.

Which expressions for Step 3 and Step 5 complete the derivation?

Step 3: Sine ( (StartFraction pi over 2 EndFraction minus x) + y )
Step 5: cos(x)cos(y) + sin(x)sin(y)
Step 3: Sine ( (StartFraction pi over 2 EndFraction minus x) + y )
Step 5: cos(x)cos(y) – sin(x)sin(y)
Step 3: Sine ( (StartFraction pi over 2 EndFraction minus x) minus y )
Step 5: cos(x)cos(y) + sin(x)sin(y)
Step 3: Sine ( (StartFraction pi over 2 EndFraction minus x) minus y )
Step 5: cos(x)cos(y) – sin(x)sin(y)

Answers

Answer:

Option (4)

Step-by-step explanation:

STEP - 1

cos(x + y)

STEP - 2

\text{sin}[(\pi)/(2)-(x+y)]

STEP - 3

\text{sin}[((\pi)/(2)-x)-y]

STEP - 4

\text{sin}((\pi)/(2)-x)\text{cos}(-y)+\text{cos}((\pi)/(2)-x)\text{sin}(-y)

STEP - 5

cos(x)cos(y) - sin(x)sin(y)

[Since, \text{sin}((\pi)/(2)-x)=cos(x) and \text{cos}((\pi)/(2)-x)=\text{sin}(x)]

[Since, cos(-x) = cos(x) and sin(-x) = -sin(x)]

Therefore, Option (4) will be the correct option.

Answer:

D

Step-by-step explanation:

Top Answer was right, don't know why it was rated poorly

Solve: 4x+3 = 2x + 9

Answers

4x+3 = 2x + 9

4x-2x=9-3

2x=6

x=6/2

x=3
Move 2x to the left hand side of the equation by subtracting 2x from both sides.
4x+3−2x=9

Add 4x and −2x to get 2x.
x+3=9

Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides.
2x=−3+9

Add −3 and 9 to get 6.
2x=6

Divide each term in the equation by 2.
x=3

x is equal to 3